Robot-assisted ureteral reconstruction for managing kidney transplant patients with ureteric complications - Dongho Shin; San Kang; Seung Ah Rhew; Chang Eil Yoon; Hyong Woo Moon; Yong Hyun Park; Hyuk Jin Cho (Investigative and Clinical Urology)
"Purpose: To evaluate the feasibility of robot-assisted ureteral reconstruction as a minimally invasive alternative to open surgery for managing ureteric complications in transplanted kidneys. Materials and Methods: From January 2020 to December 2023, robot-assisted ureteral reconstruction was performed on fifteen kidney transplant patients with vesicoureteral reflux (VUR) or ureteral stricture who had previously failed endoscopic treatments. Results: Twelve females and three males, with a mean age of 48.6±6.6 years, were included in the study. Nine patients (60.0%) underwent surgery due to VUR (grade III or higher) of the transplanted kidney, and six patients (40.0%) had transplanted ureteral strictures. Postoperative voiding cystourethrogram (VCUG) was performed at 3.2±1.6 months. Seven patients (77.8%) became VUR-free, while two patients (22.2%) had VUR regression from grade IV to I. All six patients who underwent reconstruction due to anastomosis site stricture became stenosis-free without the need for an indwelling ureteral catheter. In cases where the ureter was too short for reimplantation, a Boari flap or end-to-end anastomosis with the native ureter was performed. The mean hospital stay was 5.9±4.5 days. The urethral catheter was removed after 15.1±5.4 days, and the ureteral catheter was removed after 4.9±1.5 weeks. The mean follow-up period was 23.9±6.8 months, with no additional interventions required after surgery. No complications above Clavien-Dindo grade I were recorded. Conclusions: Robotic ureteral reconstruction is technically feasible and offers an effective, minimally invasive treatment for ureteric complications in kidney transplant patients, serving as an alternative to open surgery."